REIDENTIFIKASI DAN PEMURNIAN FUNGI ENDOFIT LBKURCC40 DARI UMBI TANAMAN DAHLIA (DAHLIA VARIABILIS) - nabella suraya (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2016)
Identification of endophytic fungi isolated from orange flowering dahlia tubers of plants from outside Padang, West Sumatra by Lorenita et al., (2013) and pre-study by researchers showed different results, so that carried serially purification. Interest purification serially performed in this study is to obtain pure isolates. Purification is done by serial dilutions ranging from 10-1-10-30 fungi spores. Identification Microscopic morphology using a light microscope Olympus CX41. The results of the purification are serially obtained two isolates, namely LBKURCC40A and LBKURCC40B, and identification of macroscopic and microscopic morphology showed LBKURCC40A and LBKURCC40B is Aspergillus sp.